Role of Nanostructures and Immunotherapies in Management of Glioblastoma Multiforme: Current Perspectives and Challenges - Trivedi, Mr. Sagar (Asian Journal of Pharmaceutics (AJP), 2022)
Glioblastoma Multiforme (GBM), a highly infiltrative grade IV primary malignant brain tumor, is characterized by poor prognosis which ultimately leads to a high mortality rate. Various restrictions such as inadequate penetration of the drug through the blood-brain barrier, active moieties falling short in achieving accumulation at tumor site, and short circulation half-life make current conventional chemotherapy insufficient in delivering the drug molecules successfully. In an attempt to overcome current modalities, nanotechnology has emerged as an alternative novel therapy for the management of GBM. Nano-therapies such as liposomes, hybrid vesicles, dendrimers, nanogels, nanorods, and nanowires have been developed for the effective treatment and diagnosis of GBM. Nano-therapies have been proven superior to conventional drug delivery due to less toxicity, higher biocompatibility, and enhanced site-specific targeting. In addition, vaccines and immunotherapy have become a promising strategy for efficacious treatment of GBM. This review provides a brief detail about numerous aspects of nano-therapies mediated treatment of GBM, associated risk, and advancement in the field of enhanced brain tumor targeting. The appraisal deals with the triggering factors responsible for GBM and treatment with various immunotherapies and vaccines and elaborates the significant progress that has been made in the arena of nanoparticles, immunotherapies, and vaccines which are implemented for combatting GBM.